Economic damage from smoking associated with four groups of chronic non-communicable diseases in the Russian Federation in 2016 - I. D. Sapunova; A. V. Kontsevaya; A. O. Myrzamatova; D. K. Mukaneeva; M. B. Khudyakov; P. V. Ipatov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Tobacco smoking is a significant behavioral modifiable risk factor (RF) for the development of chronic non-communicable diseases (CNCD). As numerous studies show, in all countries, smoking is associated with significant economic damage (ED).Aim. To evaluate ED of tobacco smoking in 2016, in the Russian Federation and costs associated with tobacco use in economy, connected with morbidity and mortality from main four groups of CNCD: cardiovascular diseases (CVD), chronic obstructive pulmonary disease (COPD), type 2 diabetes (DM2) and the main ten cancer types (CT). Material and methods. According to data on the prevalence of tobacco smoking and relative risks of large studies and meta-analyzes, the population attributive risk was calculated for four groups of CNCD: CVD, COPD, DM2 and the main ten CT. To assess ED, the proportion of each RF in morbidity and mortality was determined. The ED associatedwith tobacco smoking was calculated based on its prevalence in the Russian population according to an ESSE-RF population study.Results. The calculated population attributive risk associated with smoking in the Russian Federation (2016), in mortality for all CVDs, was 12,8%, in morbidity — 8,8%. The risk of coronary artery disease was 11,5%, stroke — 9,6%, and its mortality — 10,6% and 5,6%, respectively. The ED associated with tobacco smoking in 2016 exceeded 421,4 billion rubles (0,49% of gross domestic product). In the ED structure of the analyzed nosologies, tobacco smoking accounts for 12,41% (for CVD in general), 18,74% (for COPD), 11,32% (for DM2) and 23,13% (for bronchopulmonary CT).Conclusion. The ED of tobacco smoking amounted to 421,41 billion rubles or 0,49% of gross domestic product in 2016. Assessing of the smoking-related ED is an important argument in improving public health measures’, in favor, analysis of population measures to reduce the prevalence of smoking, determination of measures with a high practice potential in the Russian Federation, and developing proposals for their implementation.